MYC controls STING levels to downregulate inflammatory signaling in breast cancer cells upon DNA damage - Linstra, Renske; Stappenbelt, Chantal; Bakker, Femke J.; Everts, Marieke; Bhattacharya, Arkajyoti; Yu, Shibo; van Bergen, Stella D.; van der Vegt, Bert; Wisman, G. Bea A.; Fehrmann, Rudolf S.N.; de Bruyn, Marco; van Vugt, Marcel A.T.M. (The Journal of biological chemistry, 2025)
Amplification of the MYC proto-oncogene is frequently observed in various cancer types, including triple-negative breast cancer (TNBC). Emerging evidence suggests that suppression of local antitumor immune responses by MYC, at least in part, explains the tumor-promoting effects of MYC. Specifically, MYC upregulation was demonstrated to suppress the tumor-cell intrinsic activation of a type I interferon response and thereby hamper innate inflammatory signaling, which may contribute to the disappointing response to immunotherapy in patients with TNBC. In this study, we show that MYC interferes with protein expression and functionality of the STING pathway. MYC-mediated STING downregulation in BT-549 and MDA-MB-231 TNBC cell lines requires the DNA-binding ability of MYC and is independent of binding of MYC to its co-repressor MIZ1. Both STAT1 and STAT3 promote the steady-state expression levels of STING, and STAT3 cooperates with MYC in regulating STING. Conversely, MYC-mediated downregulation of STING affects protein levels of STAT1 and downstream chemokine production. Furthermore, we show that MYC overexpression hampers immune cell activation triggered by DNA damage through etoposide or irradiation treatment and specifically impedes the activation of natural killer cells. Collectively, these results show that MYC controls STING levels and thereby regulates tumor cell-intrinsic inflammatory signaling. These results contribute to our understanding of how MYC suppresses inflammatory signaling in TNBC and may explain why a large fraction of patients with TNBC do not benefit from immunotherapy.